2018
DOI: 10.1159/000487131
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Validity of Montreal Cognitive Assessment Index Scores in Mild Cognitive Impairment and Alzheimer Disease

Abstract: Background/Aims: The aim of this paper was to evaluate the incremental validity of the Montreal Cognitive Assessment (MoCA) index scores and the MoCA total score in differentiating individuals with normal cognition versus mild cognitive impairment (MCI) or Alzheimer disease (AD). Methods: Effect sizes were calculated for Alzheimer’s Disease Neuroimaging Initiative research participants with normal cognition (n = 295), MCI (n = 471), or AD (n = 150). Results: Effect sizes for the total score were large (> 0.80)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Previous research on MoCA scores has primarily focused on differences in total scores with few studies examining the utility of index scores. While it has been shown that the MoCA total score has greater incremental validity than individual index scores (Goldstein, Milloy, & Loring, 2018), others have shown the utility of the MoCA Memory Index score to discriminate between normal controls and patients with amnestic-MCI (Kaur, Edland, & Peavy, 2018). Julayanont et al (2014) showed that 90.5% of MCI participants with a MoCA Memory Index score less than 7/15 at baseline progress to AD dementia within the average follow-up period of 18 months, suggesting that the Memory Index score can be used as a predictor of progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on MoCA scores has primarily focused on differences in total scores with few studies examining the utility of index scores. While it has been shown that the MoCA total score has greater incremental validity than individual index scores (Goldstein, Milloy, & Loring, 2018), others have shown the utility of the MoCA Memory Index score to discriminate between normal controls and patients with amnestic-MCI (Kaur, Edland, & Peavy, 2018). Julayanont et al (2014) showed that 90.5% of MCI participants with a MoCA Memory Index score less than 7/15 at baseline progress to AD dementia within the average follow-up period of 18 months, suggesting that the Memory Index score can be used as a predictor of progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, both MMSE and MoCA failed to keep pace with evolving concepts regarding atypical presentations of dementia and, more specifically, with the flourishing of diagnostic criteria since 2011 [4, 5, 7]. Indeed, these tests have proven insufficient to discriminate dementia profiles since performance on their individual subtests yields limited information about specific cognitive domains [27, 28]. Addenbrooke’s Cognitive Examination is notable for having been developed originally as an expanded version of the MMSE, with the purpose to improve the differential diagnosis of dementia [29].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 A subset of the MoCA items was used as an indicator of executive function, denoted as MoCA-EF. 13 Patients with severe vision impairment were tested using the MoCA-BLIND. 14 The ILS Health and Safety subtest primarily assesses judgment and executive function via awareness of potential hazards and hypothetical management of emergencies; it is scored from 0 to 40, with higher scores indicating better performance.…”
Section: Methodsmentioning
confidence: 99%
“…Symptoms were taken from national guidelines and included GU symptoms (dysuria, frequency, suprapubic pain, gross hematuria, flank pain, and incontinence), as well as nonspecific symptoms (fever, malaise/lethargy, and confusion/altered mental status). [10][11][12][13] As a control, we collected data on other symptoms: nausea, vomiting, and abdominal pain. Trained abstractors blinded to the study hypothesis used a standardized form and code book to record data from the EMR (Epic, Epic Systems, Inc, Verona, WI) including demographics, medical history, and presence or absence of symptoms.…”
Section: Asymptomatic Bacteriuria Versus Symptom Underreporting In Olmentioning
confidence: 99%